2018
DOI: 10.1099/jmm.0.000656
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, healthcare resource utilization and overall burden of fungal meningitis in the United States

Abstract: Our study characterizes the largest longitudinal cohort of fungal meningitis in the United States. Importantly, the health economic impact and long-term morbidity from these infections are quantified and reviewed. The healthcare resource utilization of fungal meningitis patients in the United States is substantial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 63 publications
0
36
0
1
Order By: Relevance
“…For those patients receiving any treatment, the 1-year mortality rate from CM was 70% in low-income countries, 30% in Europe, and 20% in the United States ( 2 ). The morbidity and long-term health care costs (5 years postinfection) remain substantial ( 9 ). These data highlight several critical issues associated with CM treatment: (i) the need for additional therapies that can be used alone or in combination to reduce mortality rates, (ii) the need for a better global distribution of effective therapies, especially to resource-poor regions, (iii) the need for safer therapeutic options that are better tolerated, and (iv) ease-of-use considerations, such as all-oral options, especially where long-term maintenance therapy is required ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…For those patients receiving any treatment, the 1-year mortality rate from CM was 70% in low-income countries, 30% in Europe, and 20% in the United States ( 2 ). The morbidity and long-term health care costs (5 years postinfection) remain substantial ( 9 ). These data highlight several critical issues associated with CM treatment: (i) the need for additional therapies that can be used alone or in combination to reduce mortality rates, (ii) the need for a better global distribution of effective therapies, especially to resource-poor regions, (iii) the need for safer therapeutic options that are better tolerated, and (iv) ease-of-use considerations, such as all-oral options, especially where long-term maintenance therapy is required ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…AIDS was the most common underlying condition in eight patients, followed by autoimmune disorders (3), hematologic disorders (2), diabetes mellitus (DM) (1), and liver cirrhosis (1). Headache was the most common clinical presentation in 23 patients, followed by fever (19), altered consciousness (8), seizure (7), visual disturbance (7), and hearing impairment (3). Table 1 also shows comparisons between the young and non-young adult groups.…”
Section: Resultsmentioning
confidence: 99%
“…Cryptococcal meningitis (CM) caused by Cryptococcus (C.) neoformans infection is a serious infectious disease of the central nervous system (CNS) [1,2]. CM is associated with high rates of mortality and morbidity, and as with other CNS fungal infections, Therefore, CM has a severe economic impact on healthcare systems [2,3]. A paediatric study of CM from China reported that the majority of patients were apparently normal, and only 23.5% had identifiable underlying conditions [4].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to cryptococcosis and histoplasmosis, HIV/AIDS does not seem to be as strong of a predictor for Coccidioides spp. dissemination to the brain [168,179]. Underlying genetic or hormonal factors appear to be more significant susceptibility markers for coccidioidal meningitis.…”
Section: Coccidioidesmentioning
confidence: 99%
“…Underlying genetic or hormonal factors appear to be more significant susceptibility markers for coccidioidal meningitis. Diabetes [180], pregnancy [181,182], and certain ethnicities (African and Filipino descent) [183,184] all correlate with increased risk for CNS infection [137,179]. Extrapulmonary dissemination occurs in ~30% of transplant recipients with coccidioidomycosis, making it a far more frequent occurrence than in the general population [169][170][171].…”
Section: Coccidioidesmentioning
confidence: 99%